Limitations of Interlocking Features in Rotary Friction Welding (RFW) of 3D-printed PLA - Fauzan Al Fathurrahman; Fathur Rahman Naufal Santoso; Erwin; Didik Sugiyanto; Juan Pratama (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The limited build volume of fused deposition modeling (FDM) often necessitates the use of joining methods for larger components. However, the effectiveness of interlocking features in the RFW of 3D-printed polymers remains unclear. This study investigates the limitations of interlocking features in RFW of polylactic acid (PLA) by evaluating the effect of male-female geometry on the joint performance. The results show that all interlocked RFW joints exhibit significantly reduced tensile strength, reaching only approximately 30% of the control samples, accompanied by decreased ductility. Despite variations in the interlock geometry, no significant improvement in joint performance was observed. Failure analysis indicates that the excessive weld flash accumulation within the interlocking region generates internal pressure, which restricts material flow and promotes crack initiation. This leads to localized plastic deformation followed by brittle failure at the joint interface. These findings demonstrate that the interlocking geometry does not necessarily enhance joint quality in RFW of 3D-printed PLA and may introduce inherent limitations if not properly designed. This study highlights the critical role of material flow and geometric constraints in governing joint performance, emphasizing the need for optimized interlock design and process control in thermoplastic friction welding.